Pelatihan Fotografi Untuk Meningkatkan Branding dan Digital Marketing Produk UMKM Cibiru Wetan - Ramdan, Ahmad Taufiq Maulana; Lubis, Ira Aryanti Rasyi; Zubair, Feliza; Jaya, Rama Chandra; Tawaqal, Rizki Surya (Universitas Garut, 2024)
AbstractCibiru Wetan has a wealth of potential in SMEs with high-quality products, but a lack of understanding in product photography and digital marketing hinders its growth. Especially in today's digital era, with increasing online competition, strengthening branding and digital marketing is key to enhancing the visibility and sales of SME products. The crucial role of digital branding in supporting online marketing strategies is increasingly evident. The purpose of this service is to empower SMEs in Cibiru Wetan with effective photography skills and digital marketing strategies. This service employs the Participatory Learning and Action (PLA) method, or Learning by Doing, which involves participants more actively compared to conventional training. The implementation of activities is divided into several stages: education and socialization, pre-training, practice, mentoring, and evaluation. The outcome of this service is that the product photography training in Cibiru Wetan successfully improved the SMEs' ability to utilize social media for marketing. Evaluations showed a significant positive impact on participants' understanding and skills in producing attractive and professional product photos. The visual quality of product photos improved, aiding in the product's appeal on social media. Post-training monitoring indicated an increase in the frequency and quality of content, as well as more active interactions with the audience. This service can serve as a reference for similar programs in other areas and encourage policies that better support the development of SMEs through the enhancement of digital skills. Keywords: Branding; digital marketing; product photography. AbstrakCibiru Wetan memiliki banyak potensi UMKM dengan produk berkualitas tinggi, tetapi kurangnya pemahaman tentang fotografi produk dan pemasaran digital menghambat pertumbuhannya. Terutama di era digital saat ini, dengan persaingan online yang semakin ketat, memperkuat branding dan pemasaran digital menjadi kunci untuk meningkatkan visibilitas dan penjualan produk UMKM. Peran penting digital branding dalam mendukung strategi pemasaran daring semakin meningkat. Tujuan dari pengabdian ini adalah untuk memberdayakan pelaku UMKM di Cibiru Wetan dengan keterampilan fotografi dan strategi pemasaran digital yang efektif.Pengabdian ini menggunakan metode Participatory Learning and Action (PLA) atau Learning by Doing, yang melibatkan peserta lebih aktif dibandingkan pelatihan konvensional. Pelaksanaan kegiatan dibagi menjadi beberapa tahapan yaitu edukasi dan sosialisasi, pra pelatihan, praktik, pendampingan, dan evaluasi. Hasil dari pengabdian ini adalah pelatihan fotografi produk di Cibiru Wetan berhasil meningkatkan kemampuan pelaku UMKM dalam memanfaatkan media sosial untuk pemasaran. Evaluasi menunjukkan dampak positif signifikan pada pemahaman dan keterampilan peserta dalam menghasilkan foto produk yang menarik dan profesional. Kualitas visual foto produk meningkat, membantu daya tarik produk di media sosial. Pemantauan pasca pelatihan menunjukkan peningkatan frekuensi dan kualitas konten serta interaksi lebih aktif dengan audiens. Pengabdian ini dapat menjadi acuan bagi program-program serupa di daerah lain, serta mendorong kebijakan yang lebih mendukung pengembangan UMKM melalui peningkatan keterampilan digital.Kata-kata kunci: Branding; fotografi produk; pemasaran digital.